(untitled) (Journal of Applied Learning and Teaching, 2021)
Peter Fleming is a Professor at the University of Technology Sydney (UTS) Business School. He previously held positions at Cambridge University, Queen Mary University of London, and Cass Business School. Peter Fleming’s research focuses on the future of work and the ethical implications it surfaces. He is also the author of numerous books which more recently include The mythology of work, The death of homo economics, The worst is yet to come, Sugar daddy capitalism, and Dark academia. How universities die. This interview focuses on Fleming’s fairly pessimistic perspectives on the future of universities that are espoused in his most recent book, Dark academia. In a devastating critique, he argues that universities were already in crisis prior to the pandemic, but that has been exacerbated by it in the context of neoliberalism and shrinking government budgets, especially in key higher education-exporting countries such as the U.S., the UK and Australia. Apart from our focus on the state of higher education in this interview, we also, amongst other things, discuss Fleming’s nuanced critique of work (that forms the bulk of his oeuvre), his love-hate relationship with writing and other biographical snippets, as well his exciting future projects.